“Verdadeiramente este homem era justo” (Lc 23,47): a releitura lucana da imagem do justo presente no Livro da Sabedoria. - Lima, Maria Nivaneide de Abreu (2021)
“Truly this man was righteous” were the words used by the centurion when witnessing Jesus' death (Lk 23:47). Such a statement is very close to those present in the parallel accounts of the Gospels according to Mark and Matthew, with the difference that, in the Lucan work, the term “righteous” (díkaios) is used instead of “son of God” (huiós theoû). The justice of Jesus, recognized by the centurion, became a fundamental part of Christian preaching. The right term applied to Jesus appears others three times in the Lucan work: in Acts 3:14; 7:52 and 22:14. In view of this, it is worth asking: what does it mean to be righteous? The notion of justice and the understanding of who is righteous in the Bible developed over time, with the change where each text appears and consequently, from the perspective of each author, new meanings and nuances. With this research, it is intended to demonstrate that the image of the righteous person present in the Book of Wisdom underlies the understanding of the righteous person present in Luke-Acts, especially in the designation of Jesus as righteous in Lk 23:47. The methodology used in this work consisted of the analysis of biblical texts and bibliographical research, and was carried out in four stages: initially, the notion of justice and righteousness in the Old Testament literature was presented; then, a more accurate look was taken to the Book of Wisdom, in order to identify the image of righteous present there; in a third moment, it turned to the representation of the righteous in Lucan's work; and finally Wisdom and Luke-Acts were put side by side. Comparing the two works, and specifically the concept of the righteous that emerges in Wisdom and Luke-Acts, one can glimpse many aspects of continuity, such as the fact that in both cases the righteous places himself in the long tradition of the righteous sufferer and knows himself to be a child of God. One can, however, highlight an aspect of discontinuity: Jesus, in Lucan's work, is the righteous man who does not cease his ministry even during his passion. Unlike the righteous presence in Wisdom, Jesus heals and forgives while suffering and dying. He is not a victim but a martyr, a child of God, whose communion with the Father remains unshakable even in the face of death.